Respuesta :

Answer:

2/(x²-5)+3x(x²-5)

Step-by-step explanation:

Mark as brainlest answer

Ver imagen Аноним

Answer:

[tex]\left(f\:\circ \:g\right)\left(x\right)=\quad3x^2-13[/tex]

(3x² - 13)

Step-by-step explanation:

[tex]\left(f\:\circ \:g\right) = f(g(x))[/tex]

f(x) = 3x + 2

g (x) = x² - 5

substitute values:

f ( g ( x ) )

{plug in "g(x)" as the x in f(x)}

3x + 2

3(x² - 5) + 2   {distribute 3 to x² and -5}

3x² - 15 + 2  {combine like terms}

3x² - 13

[tex]\left(f\:\circ \:g\right)\left(x\right)=\quad3x^2-13[/tex]

(3x² - 13)

hope this helps!! :)

ACCESS MORE